Perilaku Ibu dalam Pemenuhan Imunisasi Dasar Lengkap Bayi pada Masa Pandemi COVID-19 - Puspitasari, Nimas Tunjung; Indarjo, Sofwan (Center for Public Health Nutrition Studies, Universitas Negeri Semarang, Indonesia, 2023)
Background: COVID-19 pandemic has caused various kinds of disruptions, including immunization services. In the working area of the Mijen Healthcare Center, as of August 2021, around 42,4% of the target babies have just received complete basic immunizations. This study aims to determine the factors related to mother’s behavior fulfill complete basic immunization of infants during COVID-19 pandemic. Methods: This type of research is observational analytics using a cross sectional design. The sample in this study was 147 mothers who had babies aged 9-11 months using purposive sampling technique. The instrument used was a questionnaire. Data were analyzed using Chi Square test and fisher test (α= 0,05). Results: There is a relationship between level of knowledge (p = 0.037) and attitude (p = 0.010) with mother’s behavior fulfill complete basic immunization of infants. There is no relationship between age (p-value = 0,543), education level (p-value = 0,485), job (p-value = 0,459), parity (p-value = 0,093), family support (p-value = 0,491), health cadres support (p-value = 0,980), health workers support (p-value = 0,506), and source of information (p-value = 0,399) with mother’s behavior fulfill complete basic immunization of infants. Conclusion: There is a significant relationship between are knowledge and attitudes with mother’s behavior in completeness basic immunization during COVID-19 pandemic.